Solar light-driven CoFe2O4/α-Ga2O3 heterojunction nanorods mediated activation of peroxymonosulfate for photocatalytic degradation of norflurazon. Issue 5 (October 2021) - Rajangam, R.; Pugazhenthiran, N.; Krishna, S.; Mangalaraja, R.V.; Valdés, H.; Ravikumar, A.; Sathishkumar, P.
Abstract: Low frequency (40 kHz) ultrasound-assisted technique was utilized in the synthesis of CoFe2 O4, GaOOH and α-Ga2 O3 nanorods. CoFe2 O4 was tethered successfully at the crystal matrices of GaOOH and α-Ga2 O3 nanorods to form heterojunction nanocatalysts (CoFe2 O4 /GaOOH; CoFe2 O4 /Ga2 O3 ). The heterojunction nanocatalysts were characterized using various analytical tools to confirm the expected modifications. The band gap of GaOOH (Eg = 4.50 eV) and α-Ga2 O3 (Eg = 4.46 eV) are reduced in the formed heterojunction nanocatalysts CoFe2 O4 /GaOOH (Eg =2.56 eV) and CoFe2 O4 /Ga2 O3 (Eg = 2.51 eV), respectively. Moreover, the XRD and HR-TEM analyses demonstrate the formation of heterojunction nanocatalysts composed of the lattice diffusion of Co and Fe of CoFe2 O4 into the matrix of α-Ga2 O3 nanorods with good crystallinity. The photocatalytic efficiency was assessed during solar light-driven photocatalyic oxidation of norflurazon in single treatments and also assisted by peroxymonosulfate addition. The experimental results indicate that 98% of the norflurazon (NRF) is oxidized within 40 min of solar light irradiation in the presence of CoFe2 O4 /α-Ga2 O3 heterojunction nanophotocatalyst, having higher photocatalytic efficiency than benchmarked TiO2 nanoparticles (Degussa P25). Moreover, the results also show that the addition of peroxymonosulfate (PMS) boosts the photocatalytic oxidation and achieving 99% NRF oxidation within 10 min of solar light irradiation by the generation of SO4 − and OH radicals. The novel synthesized heterojunction nanophotocatalyst (CoFe2 O4 /α-Ga2 O3 ) results to be highly stable after six consecutive operating cycles. Graphical Abstract: ga1 Highlights: Efficient heterojunction CoFe2 O4 /α-Ga2 O3 solar light-driven catalyst was synthesized. Radical generation was quantified using photoluminescence studies. Norflurazon was mineralized in the presence of CoFe2 O4 /α-Ga2 O3 nanorods CoFe2 O4 /α-Ga2 O3 was magnetically recovered and reused in six consecutive cycles A suitable mechanism was proposed for the degradation of norflurazon.